A Decision-Making Carbon Reinforced Material Selection Model for Composite Polymers in Pipeline Applications - Mohammed Ahmed Mustafa; S. Raja; Layth Abdulrasool A. L. Asadi; Nashrah Hani Jamadon; N. Rajeswari; Avvaru Praveen Kumar (Advances in Polymer Technology)
Pipes are manufactured primarily through the extrusion process. One of the material extrusion processes in recent digital manufacturing is additive manufacturing’s fusion deposition modeling. Pipes are made from various materials such as metal and plastic/polymers, and the main challenge has been in selecting the pipe material for the customized application. For the creation of water-passing tubes, this research has chosen appropriate carbon-reinforced polymers that can be used with filament made of polyether ether ketone (PEEK) and polyethylene terephthalate glycol (PETG). For this goal, the analytical hierarchy process, also known as the AHP, is used to choose the best material based on factors such as cost, temperature resistance, printing speed, and mechanical properties of the material. The results revealed that PEEK-CF is a better material for the customized impeller application than PETG-CF. The PEEK-CF obtains the higher priority value of 0.6363, and the PETG-CF obtains 0.2791. This decision-making technique can be used to select other comparable customized applications.